Ethnobotanical study on medicinal wild plants sold at the Brikama market in The Gambia (CaJoST, 2023)
Herbal markets, in turn, not only supply herbal treatment for diseases but also conserve biocultural diversity by transferring traditional knowledge to future generations. the aim of this study was to identify and document the vernacular names and therapeutic uses of wild medicinal plants species sold and used by the people of Brikama in the West Coast Region of The Gambia. An ethnobotanical survey was conducted to document the wild medicinal plants sold at the Brikama market. The study was carried out between June and July 2023 using semi-structured interviews with 50 market vendors and 20 clients (laypeople) who uses traditional medicines from different age groups in mandinka local language. The survey identified and recorded 71 plants species from 41 plant families, used for treating diseases in Brikama and its surroundings. The Fabaceae was the most represented plant family and most of the plants were trees and the leaves were the most commonly used plant part 51% followed by shrubs 38% and herbs 11%. Knowledge of the use of plants as medicines remains generally with the older generation with few youths showing an interest. The youth should be encouraged to learn the traditional medicinal knowledge to preserve it from being lost with the older generation. There is need to encourage the domestication and cultivation of medicinal plants as well as put in place conservation measures to ensure sustainability of their usage.